Colony Development and Density-Dependent Processes in Breeding Grey Herons - Takeshi Shirai (International Journal of Zoology)
The density-dependent processes that limit the colony size of colonially breeding birds such as herons and egrets remain unclear, because it is difficult to monitor colonies from the first year of their establishment, and the most previous studies have considered mixed-species colonies. In the present study, single-species colonies of the Grey Heron (Ardea cinerea) were observed from the first year of their establishment for 16 years in suburban Tokyo. Colony size increased after establishment, illustrating a saturation curve. The breeding duration (days from nest building to fledging by a pair) increased, but the number of fledglings per nest decreased, with colony size. The reproductive season in each year began earlier, and there was greater variation in the timing of individual breeding when the colony size was larger. The prolonged duration until nestling feeding by early breeders of the colony suggests that herons at the beginning of the new breeding season exist in an unsteady state with one another, likely owing to interactions with immigrant individuals. Such density-dependent interference may affect reproductive success and limit the colony size of Grey Herons.